Contemporary Music and Its Challenges for Music Theory (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2018)
Contemporary music has found different ways in order to realize new methods of compositions in a process of indiviulazitation. Many of its phenomenons such as the abandonment of functional tonality have already been announced by composers such as Richard Wagner and during its development many scholars have come up with different systems in order to add something new to the existing material. The variety of new models such as the center tone-theory or open forms have a new challenge for music theory, which was used to give accurate definitions of a common denominator. This article wants to analyze those new methods and the importance to understand them in order to be able to give a clear analysis.